Os saberes em potencial da atividade policial ostensiva: sistematizando modelos a partir da experiência potiguar - Silva, Sairo Rogério da Rocha e (2007)
This work of research presents an investigation into the knowledge related to the ostensive policing activities of a group of the Rio Grande do Norte State Military Police Captains. This knowledge, which is decisive and part of Brazilian Military Police Constitutional matters, must be taken into consideration when it comes down to planning and putting into force the services related to ostensive public security. Thus, a historical and social analysis about the formation of the police by starting from foreigner experiences down to Rio Grande do Norte s reality, led by such knowledge, was made. Further, studying Brazilian and local scene, this knowledge was analyzed on the ostensive policing activities as for the principles of the Brazilian National Public Security Plan, Brazilian Classification of Occupations / CBO 2002, the reference documents and studies for police graduation Curricular Basis and Matrix; the Variables of Ostensive Policing, as well as some important competences of police service. Arguing that this knowledge is somehow related to what is presented in this work as Orientation Axis to Military Police Service , research tools such as Critical Case Solution and the answers to the Questionnaire on Fundamental Areas of Military Police Service , having in the end six knowledge models related to ostensive policing activities were used within that group. This knowledge can be classified in three distinct categories of connotations within the military police activity: one with reactive/repressive characteristics being the most predominant; the second as preventive; and another one that revealed that the military police activity is being misused for actions and/or missions outside the scope of action of military police